Uncooled Wide-Range Spectral Optoelectronic Devices on the Base of HgCdTe Semiconductor - Sizov, F. (Ukrainian Journal of Physics, 2019)
Issues associated with the development and the exploitation of infrared (IR) and sub-terahertz (THz) radiation detectors based on HgCdTe semiconductor are discussed. It is shown that this mercury cadmium telluride (MCT) semiconductor can be applied to the development of bi-colour detectors operating in the IR and sub-THz spectral ranges.